2017
DOI: 10.1177/0892705717743292
|View full text |Cite
|
Sign up to set email alerts
|

Investigating mechanical, thermal, and flammability properties of thermoplastic polyurethane/carbon nanotube composites

Abstract: Thermoplastic polyurethane (TPU) composites containing carbon nanotube (CNT) with the loading ratios from 0.5wt% to 2 wt% were prepared using melt-compounding process. Surfaces of the CNT particles were treated with sulfuric acid/nitric acid to purify CNT and to achieve compatible surface characteristics between TPU matrix and CNT. Mechanical, thermal, flame retardant, melt flow, and morphological properties of TPU/CNT composites were investigated. Addition of CNT to TPU matrix causes in a prominent increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 53 publications
3
35
0
1
Order By: Relevance
“…The black color of C 60 is the main reason for this observation which leads to increase in absorption of radiant heat within the top layer of the material. 52,53 Similar observations were reported when the other carbonaceous materials were used as flame retardant additives including carbon nanotube, 54 expandable graphite, 55 and carbon fiber 56 in our previous studies and graphene nanosheets, 57 and carbon nanofiber 58 in the literature, additionally. The earlier initiation of thermal degradation of TPU occurs thanks to the higher heat absorption.…”
Section: Resultssupporting
confidence: 84%
“…The black color of C 60 is the main reason for this observation which leads to increase in absorption of radiant heat within the top layer of the material. 52,53 Similar observations were reported when the other carbonaceous materials were used as flame retardant additives including carbon nanotube, 54 expandable graphite, 55 and carbon fiber 56 in our previous studies and graphene nanosheets, 57 and carbon nanofiber 58 in the literature, additionally. The earlier initiation of thermal degradation of TPU occurs thanks to the higher heat absorption.…”
Section: Resultssupporting
confidence: 84%
“…Normally, the addition of a filler to polymeric matrices limits their free mobility, increasing the material’s apparent viscosity. Actually, the effect of fillers on the reduction of MFI has been reported by several authors [ 42 , 43 , 44 ]. However, the addition of C- g -PMMA content only caused a slight reduction in the MFI to 6.2 g·10 min −1 (a reduction around 7%), which can be associated with the better compatibility between the filler and the matrix.…”
Section: Resultsmentioning
confidence: 98%
“…29 Kanbur and Tayfun showed that the addition of CNT in polyurethane with the loading from 0.5 wt% to 2 wt% causes to enhance in tensile strength, percentage of elongation at break, and tensile modulus values of polyurethane. 30…”
Section: Introductionmentioning
confidence: 99%